SISTEM PEMELIHARAAN MENARA BTS (BASE TRANSCEIVER STATION) BERBASIS MOBILE - Sucipto, Adi; David, Hufajar Wiliam; Riskiono, Sampurna Dadi; Ahdan, Syaiful (STMIK Palangkaraya, 2022)
The development of mobile device technology, especially Android applications, is growing very significantly. The focus of this research is how to build a mobile-based BTS (Base Transceiver Station) tower maintenance system. This system was built to simplify and speed up the documentation and reporting process for BTS tower maintenance, thereby minimizing loss and duplication of documentation files when performing maintenance. This system is built using the Java programming language with a Firebase database. The system development method used is Extreme Programming. System testing using ISO 25010 testing using three testing aspects, with the results: 100% functionality aspect, 89.00% usability, and 5.4% CPU usage performance efficiency. Tests were carried out on 5 Android Mobile devices with different specifications. From the results of testing on respondents using a Likert measurement scale, it was obtained an average of 94.5%. Based on this, it can be concluded that the system is very good/very feasible to use and provides solutions to the problems faced.